Legal Counseling On The Mediation Process In Land Dispute Resolution In Serdang Bedagai Regency - Winta Hayati; Oktavianto Setyo Nugroho; Khomaini Khomaini; Ramadhany Nasution; Syaipul Puad Tarigan; Saimah Rambe; Andalan Christian Saputra Hia (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Land disputes are a complex issue that frequently occurs in Serdang Bedagai Regency, rooted in unclear ownership status, overlapping certificates, and improper transfer of rights. These issues not only cause material losses but also trigger social tensions in the community. The problem faced by the community is a lack of understanding of the mediation process as a more effective and efficient alternative dispute resolution compared to litigation. People tend to choose the court route, which is time-consuming, expensive, and can worsen relations between parties. To address these problems, legal counseling activities were conducted in Pematang Kuala Village through a collaboration between the community service team of the Indonesian Community Development University (UPMI), Ismayani and Partners Legal Consultants, and media partner sinarsergai.com. The implementation methods included interactive lectures, group discussions, and presentations of real-life case studies. The material covered the legal basis for mediation based on Law No. 30 of 1999 and Perma No. 1 of 2016, the stages of the mediation process, the role of mediators, and the advantages of mediation over litigation. The results of the activities showed an increase in community understanding of mediation and the establishment of a sustainable referral system. This program is expected to reduce land conflicts through win-win solutions, accelerate the dispute resolution process, and improve social harmony in Serdang Bedagai Regency.